Предмет: Алгебра, автор: danilbelozyorov71

Помогите решить производные функции​

Приложения:

Ответы

Автор ответа: Miroslava227
2

Ответ:

а)

f'(x) = 1

б)

f'(x) = 2(3x + 1) + 3(2x - 3) = 6x + 2 + 6x - 9 = 12x - 7

в)

f'(x) =  \frac{5(1 - 3x) + 3(5x + 3)}{ {(1 + 3x)}^{2} }  =  \frac{5 - 15x + 15x + 9}{ {(1 - 3x)}^{2} }  =  \frac{14}{ {(1 - 3x)}^{2} }

г)

f'(x) =  \frac{ \frac{3}{ 2 }  {x}^{  - \frac{1}{2} }(2 +  \sqrt{x} ) -  \frac{1}{2}   {x}^{ -  \frac{1}{2} }  }{ {(2 +  \sqrt{x}) }^{2} }  =  \frac{ \frac{3(2 +  \sqrt{x} )}{2 \sqrt{x} } -  \frac{1}{2 \sqrt{x} }  }{ {(2 +  \sqrt{x}) }^{2} }  =   \\  = \frac{3}{2 \sqrt{x} {(2 +  \sqrt{x}) }^{2}  }  -  \frac{1}{2 \sqrt{x}  {(2 +  \sqrt{x}) }^{2} }

___________________________

а)

f'(x) =  \frac{ \cos(x)(1 -  \sin(x))   +   \cos(x)(1 +  \sin(x))    }{ {(1 -  \sin(x)) }^{2} }  =  \\  =  \frac{ \cos(x) -  \sin(x) \cos(x)  +  \cos(x)  +  \sin(x)  \cos(x)   }{ {(1 -  \sin(x)) }^{2} }  =  \frac{2 \cos(x) }{ {(1 -  \sin(x)) }^{2} }

б)

f'(x) =  \cos(2 {x}^{2}  - 5)  \times 4x

в)

f'(x) =  -  \sin( {x}^{3} - 3 )  \times 3 {x}^{2}

г)

f'(x) =  \frac{1}{ { \cos}^{2}(x) }  \times  { \cos }^{2} (x) + 2 \cos(x)  \times ( -  \sin(x) ) \times tg(x) =  \\  = 1 - 2 { \sin }^{2} (x) =  \cos(2x)

___________________________

а)

f'(x) = 100 {(3 - 5x +  {x}^{2}) }^{99}  \times (2x - 5)

б)

f'(x) = 5 \times  \frac{3}{5}  {x}^{ -  \frac{2}{5} }  =  \frac{3}{ \sqrt[5]{ {x}^{2} } }

в)

f'(x) \frac{4 {x}^{2}  \times \sqrt[3]{x}  -  \frac{1}{3}  {x}^{ -  \frac{2}{3} } \times   2{x}^{3}  }{ \sqrt[3]{ {x}^{2} } }  =  \\  =  \frac{4 {x}^{2}  \sqrt[3]{x} -  \frac{2 {x}^{3} }{ 3 \sqrt[3]{ {x}^{2} }  }  }{ \sqrt[3]{ {x}^{2} } }  =  \\  =  \frac{4 {x}^{2}  \sqrt[3]{x} }{ \sqrt[3]{ {x}^{2} } }  -  \frac{2 {x}^{3} }{3 \sqrt[3]{ {x}^{2} }  \times  \sqrt[3]{ {x}^{2} } }  =  \\  = 4x \sqrt[3]{ {x}^{2} }  -  \frac{2}{3} x \sqrt[3]{ {x}^{2} }

г)

f'(x) = (3 {x}^{ \frac{7}{3} } )' = 7 {x}^{ \frac{4}{3} }  = 7x \sqrt[3]{x}

__________________

а)

f'(x) = 1 +  \frac{1}{x}

б)

f'(x) =  ln(3)  \times  { 3 }^{2 {x}^{2} }  \times 4x

в)

f'(x) = 2 ln(5)  \times  {5}^{x}  + 3 {e}^{x}

г)

f'(x) =  \frac{ {e}^{x} ( {e}^{x} - 1) -  {e}^{x}(1 +  {e}^{x} )  }{ {( {e}^{x}  - 1)}^{2} }  = \\  =   \frac{ {e}^{x}( {e}^{x} - 1 -  {e}^{x}   - 1) }{ {( {e}^{x} - 1) }^{2} }  \\  =  \frac{ - 2 {e}^{x} }{ {({e}^{x}  - 1)}^{2} }


danilbelozyorov71: спасибо)
Похожие вопросы
Предмет: Биология, автор: Rudeblad